Analisis Konsumsi Pangan Masyarakat Provinsi Sumatera Barat - Zikri Mubarak; Gusriati; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2022)
The purpose of this study was to determine the Expected Food Pattern Score in West Sumatra in 2000-2019, and to find out whether the factors of per capita income, food consumption expenditure, population, inflation affect the Expected Food Pattern Score in West Sumatra. This research was conducted from April 2021 to May 2021. The location determination was purposive, the data used was secondary data. The basic method used in this research is descriptive analytical method using time series data. The analysis used is Multiple Linear Regression analysis. The results show that the PPH score in West Sumatra Province from 2000-2019 has increased by 134.58% with an annual average of 6.72%, the variable that has a significant effect on the PPH score in West Sumatra Province partially is the variable total population. Meanwhile, simultaneously (simultaneously) are the variables of income per capita, food consumption expenditure, population and inflation (sig 0.000 <0.05). The coefficient of determination (R2) in this study was 0.82